The year in cardiology: arrhythmias and pacing - Camm, A. John; Lip, Gregory Y.H.; Schilling, Richard; Calkins, Hugh; Steffel, Jan (SA Heart Journal, 2020)
During this last year, there has been much progress with regard to anticoagulant and ablation therapy for atrial fibrillation (AF). Apart from recently issued European Society of Cardiology Guidelines for the management of patients with supraventricular arrhythmias, there has been little progress in research in this field. Ventricular arrhythmias and device therapy have seen modest progress.